Oral Presentations Abstracts: ETHICAL ISSUES RELATING TO PRENATAL GENETIC TESTING - PERROT, Adeline; HORN, Ruth (Studia Universitatis Babeş-Bolyai Bioethica, 2021)
View of Volume 66, Special Issue, September 2021 Introduction: Non-invasive prenatal testing (NIPT) is a rapidly developing genomic technology that is constantly widening its scope and opening up new possibilities in reproductive medicine. Ten years after NIPT has been made commercially available, it is increasingly entering routine antenatal care as either a first- or second-tier test. In England, France and Germany, for example, NIPT has been made available free-of-charge as a second-tier test to women with a higher chance of common chromosomal anomalies. The clinical implementation of NIPT carries benefits but also raises important ethical questions. Our project analyses these questions within their specific contexts in England, France and Germany. Methods: As part of a wider research project, which will involve qualitative methods, we conducted a document analysis to compare arguments about, and regulations governing NIPT in the three countries in: law and policy document; public reports; medical press; academic literature; and media. Results: Despite the similarities between the three countries to offer NIPT as a second-tier screening tool, they exhibit differences with regard to their public discourses about prenatal genomics, screening policies, the risk-thresholds they use, professional regulations and laws. These differences have an impact on the way ethical issues emerge, and questions about the meaning of health, illness and disability, the scope of public health interventions, social inclusion and exclusion as well as reproductive choice are approached in each country.